2011
DOI: 10.1007/s13361-011-0254-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of C-Terminal Residue Exclusion in Peptide Fragmentation by ESI and MALDI Tandem Mass Spectrometry

Abstract: By screening a data set of 392 synthetic peptides MS/MS spectra, we found that a known C-terminal rearrangement was unexpectedly frequently occurring from monoprotonated molecular ions in both ESI and MALDI tandem mass spectrometry upon low and high energy collision activated dissociations with QqTOF and TOF/TOF mass analyzer configuration, respectively. Any residue localized at the C-terminal carboxylic acid end, even a basic one, was lost, provided that a basic amino acid such arginine and to a lesser extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
(140 reference statements)
0
21
0
Order By: Relevance
“…The dissociated precursor ions (m/z 689.4 for protonated AWSVAR, m/z 1439.8 for protonated RHPEYAVSVLLR and m/z 1479.8 for protonated LGEYGFQNALIVR) were also satisfying the fragmentation rules [49]. An abundant loss of the C-terminal residue (R) was observed for the second peptide (RHPEYAVSVLLR) corresponding to a miscleavage [40] as seen in Fig. S4b together with the loss of a neutral molecule from the arginine sidechain as depicted previously in the literature [39].…”
Section: 5mentioning
confidence: 88%
See 2 more Smart Citations
“…The dissociated precursor ions (m/z 689.4 for protonated AWSVAR, m/z 1439.8 for protonated RHPEYAVSVLLR and m/z 1479.8 for protonated LGEYGFQNALIVR) were also satisfying the fragmentation rules [49]. An abundant loss of the C-terminal residue (R) was observed for the second peptide (RHPEYAVSVLLR) corresponding to a miscleavage [40] as seen in Fig. S4b together with the loss of a neutral molecule from the arginine sidechain as depicted previously in the literature [39].…”
Section: 5mentioning
confidence: 88%
“…The first peptide of the β chain [461-468] (m/z 1049.6, IRPYFPEQ) was the result of a trypsin miscleavage, an arginine residue being present within the sequence. As recently reported, such arginine-containing sequence is prone to a C-terminal rearrangement leading to the abundant loss of the C-terminal residue providing a truncated peptide ion referred as a 'b n − 1 + H 2 O' fragment ion [40]. This behavior was also here observed from NanoSi deposit in LDI-MS/MS, the Cterminal glutamine (Q) residue being excluded from the protonated precursor ion to give an abundant b 7 + H 2 O (m/z 1049.6 → m/z 921.6) as displayed in Fig.…”
Section: 5mentioning
confidence: 96%
See 1 more Smart Citation
“…Several characteristic PSD ions have been reported for modified peptides, such as peptides that are phosphorylated at Ser or Thr, oxidized at Met, sialylated at a glycosylated residue, etc. Other than these, loss of a C‐terminal AA residue via C‐terminal rearrangement from the PSD ion by metastable decomposition is prominently observed for peptides that contain Arg residues(s) in the sequence, and this is particularly useful for database searching based on the MS/MS spectrum as well as for the determination of the C‐terminal AA. The ions that are produced in the time span of the flights in a field‐free region (the space between the exit of the ion source and the inlet of a reflectron in the instrument used in this study) are observed as broad, poorly resolved peaks with m / z values that are slightly higher than the theoretical values, unless the reflectron is electronically tuned taking the kinetic energies of those ions into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence‐specific fragmentation such as the loss of the C‐terminal amino acid (AA) residue from a peptide via an intramolecular rearrangement upon collision‐induced dissociation (CID) or metastable decomposition has been reported . The basicity and the position of a basic AA in the sequence, particularly arginine (Arg), are critical for the rearrangement to occur at the C‐terminus, generating a [ b n −1 + H 2 O] ([ b n −1 + 18]) ion .…”
Section: Introductionmentioning
confidence: 99%